Sintesis Surfaktan Natrium Lignosulfonat (C20H24Na2O10S2) Berbahan Dasar Serbuk Kayu Mahoni Menggunakan Proses Sulfonasi. - Maulida, Nabilah; Aisah; Perwitasari, Dyah Suci; Siswati, Nana Dyah; Sani (Jurnal Fisika Unand, 2025)
Furniture production made from mahogany wood produces sawdust that contains biomass such as cellulose, hemicellulose, and lignin. The lignin content in mahogany wood can be used as raw material for making sodium lignosulfonate surfactants. Delignification of lignin is carried out alkaline and continued with lignin isolation by acid precipitation. Pure lignin isolate is further used as a raw material for making sodium lignosulfonate surfactants using the sulfonation process. The sulfonation process is carried out by mixing lignin isolate and sodium bisulfite solution using excess NaHSO3 variation and sulfonation time. Both variables are run by adding sodium hydroxide as a catalyst and the pH condition was maintained at pH 4. The sodium lignosulfonate surfactant solution formed was then characterized using FT-IR spectrophotometer and UV-Vis spectrophotometer. The best condition was obtained at a sulfonation time of 150 minutes and NaHSO3 exceeded 75%, namely with a surfactant concentration of   4100,784 mg/L.